Ceftazidime-avibactam susceptibility against Escherichia coli and Klebsiella pneumoniae - Arun Sachu; Alice David (Iranian Journal of Microbiology)
Background and Objectives: Carbapenem-resistant Enterobacteriaceae (CRE) infections are extremely difficult to treat and have a high fatality rate. The study's primary goal was to determine the rate of ceftazidime-avibactam susceptibility using disc diffusion and E-Test, as well as to evaluate the agreement between the two methods. Materials and Methods: A total of 124 multidrug-resistant (including carbapenem) Escherichia coli and Klebisella pneumoniae isolates were included. Kirby Bauer's disc diffusion and E-test were used as the testing methods in this study. Results: In this study 37.5% and 33.9% of the isolates were susceptible to ceftazidime-avibactam by E test and Disc diffusion respectively. There were five isolates which produced discordant results. Among the 56 isolates there was 91% agreement between the two methods. Conclusion: Among the discordant isolates the alarming disparity in zone size was a significant concern. Since CRE infections are very common, an economical and practical method for testing ceftazidime-avibactam susceptibility is needed in all the clinical microbiology laboratories as it is a last resort drug.